2003
DOI: 10.1067/mtc.2003.57
|View full text |Cite
|
Sign up to set email alerts
|

Results of surgery for aortic root aneurysm in patients with Marfan syndrome

Abstract: This study suggests that aortic valve-sparing operations provide similar survival but lower rates of valve-related complications than aortic root replacement for patients with Marfan syndrome. Reimplantation of the aortic valve may be more appropriate than remodeling of the aortic root to prevent dilation of the aortic annulus, and for this reason we now use only this technique to treat patients with Marfan syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
131
1
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(149 citation statements)
references
References 25 publications
12
131
1
4
Order By: Relevance
“…There were 2 studies reporting the outcomes of CVG only (11,19) and 8 studies reporting the outcomes of VSRR only (15,17,20,22,23,26,28,31). Thirteen studies reported outcomes for both CVG and VSRR (12)(13)(14)16,18,21,24,25,27,29,30,32,33). The overall study characteristics are detailed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…There were 2 studies reporting the outcomes of CVG only (11,19) and 8 studies reporting the outcomes of VSRR only (15,17,20,22,23,26,28,31). Thirteen studies reported outcomes for both CVG and VSRR (12)(13)(14)16,18,21,24,25,27,29,30,32,33). The overall study characteristics are detailed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…There are also histologic and biochemical data that suggest that the medial abnormalities of the aortic wall and elastin abnormalities of the aortic wall are no different between those with an aortic root aneurysm without phenotypic characteristics of a connective-tissue disorder compared with those with a connective tissue disorder. 2,3 De Oliveira et al 24 reported on 61 Marfan syndrome patients undergoing a valve-preserving reconstruction compared with 44 patient having a composite reconstruction. Freedom from reoperation at 10 years was 100% in the valve-preserved group.…”
Section: Discussionmentioning
confidence: 99%
“…39 Alternative procedures include the Bentall composite graft repair, in which both the aortic root and the aortic valve are replaced, or a valve conserving technique such as re-implantation of the native aortic valve in a Dacron tube (described by David) or remodelling of the aortic root (described by Yacoub). 40,41 The Bentall procedure has a low mortality in experienced hands with long-term survival of around 80% at 5 years and 60% at 10 years, 42 but requires lifelong anti-coagulation post-operatively, whereas valve conserving techniques may avoid the need for anticoagulation. Use of a valve-conserving procedure has been controversial as it is suggested that further deterioration of the aortic valve leaflets will require later valve replacement surgery.…”
Section: Cardiovascular System In Marfan Syndromementioning
confidence: 99%